Glaucoma and microglia-induced neuroinflammation - Ishikawa, Makoto; Izumi, Yukitoshi; Sato, Kota; Sato, Taimu; Zorumski, Charles F.; Kunikata, Hiroshi; Nakazawa, Toru (Frontiers in Ophthalmology, 2023)
Abstract Glaucoma is a multifactorial neurodegenerative disease characterized by a progressive optic neuropathy resulting in visual field defects. Elevated intraocular pressure (IOP) is the greatest risk factor for the development of glaucoma, and IOP reduction therapy is the only treatment currently available. However, there are many cases in which retinal degeneration progresses despite sufficient control of IOP. Therefore, it is important to elucidate the pathophysiology of glaucoma that is resistant to current IOP lowering therapies. Experiments using animal glaucoma models show the relationships between microglial neuroinflammatory responses and damage of retinal ganglion cells (RGCs). Inhibition of neuroinflammatory pathways associated with microglial activation appears to be neuroprotective, indicating that microglia may be an important therapeutic target for RGC protection. In this review, we will focus on microglia-induced neuroinflammation in the pathogenesis of glaucoma to offer new insights into the possibility of developing novel neuroprotective therapies targeting microglia.